THE USE OF CONNOTATIVE MEANING DERIVED FROM DARWIS TERE LIYE’S QUOTES ON FACEBOOK - RizkaZulhaini; Muhammad Natsir (State University of Medan, 2015)
The study deals with the use of connotative meaning especially inDarwisTereLiye’s quotes. In this study the researcher focuses on the three maintypes of connotative meaning namely positive connotative, negative connotativeand neutral connotative. The data that support this study are obtained by applyingdescriptive qualitative method by selecting and then analyzing some quotes ofDarwisTereLiye on facebook. The findings show that there are three types ofconnotative meaning in DarwisTereLiye’s quotes. There are positive connotative,negative connotative and neutral connotative. Positive connotative as thedominant type that found in this research.